Management IMPACT OF SOCIAL MEDIA MARKETING AND BRAND AWARENESS ON PURCHASE INTENTION IN COFFEE SHOP CULINARY IN SURABAYA - GS, Achmad Daengs (LPPM of NAROTAMA UNIVERSITY, 2023)
ABSTRACT Purpuse: to explain the Effect of Social Media Marketing and Brand Awareness on Purchase Intention Design/methodology/approach: Analysis techniques using Partical Least Square (PLS) and assisted by SmartPLS 3.0 software. Findings: Social Media Marketing and Brand Awareness have a positive and significant effect on the Purchase Intention of Coffee Shop Culinary in Surabaya so it is recommended to increase Social Media Marketing can be done to create Coffee Shop Culinary social media to expand Coffee Shop Culinary promotion and establish relationships with customers or other companies. Meanwhile, to increase Brand Awareness, you can provide promotions and discounts on products purchased by consumers and promote with Influencer Marketing to attract consumers to Coffee Shop Culinary in Surabaya. Practical implications: improving Social Media Marketing can be done by creating Culinary Coffee Shop social media to expand Coffee Shop Culinary promotion and establish relationships with customers Originality/value: This paper is original Paper type: research paper Keywords: Social Media Marketing, Brand Awareness, Purchase Intention.